Oscilação paramétrica: dinâmica populacional de polaritons em uma microcavidade - Marina Bezerra Eiras da Silva (2013)
This dissertation aims to report the study of the polariton population dynamics derived from a quantum model for parametric oscillation. In this work we show the experimental results of the measurement of the oscillation period of polaritons between excited states and the bottom state of its dispersion curve. There was a variation of the polarization of the pulsed laser, which was used to excitate the system. The pump and probe experimental method was adopted to obtain the necessary time resolution. It was also tested the dependency of the oscillation period with the power of excitation and the microcavity detuning.